2020
DOI: 10.1186/s13046-020-01692-x
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic flux inhibition enhances cytotoxicity of the receptor tyrosine kinase inhibitor ponatinib

Abstract: Background Despite reported advances, acquired resistance to tyrosine kinase inhibitors still represents a serious problem in successful cancer treatment. Among this class of drugs, ponatinib (PON) has been shown to have notable long-term efficacy, although its cytotoxicity might be hampered by autophagy. In this study, we examined the likelihood of PON resistance evolution in neuroblastoma and assessed the extent to which autophagy might provide survival advantages to tumor cells. Methods The effects of PON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In our study, an increase of LC3II/I ratio was found in both LSCC cell lines treated with PI3K or mTOR inhibitors, among which the dual inhibitor NVP-BEZ235 is the most significant, supporting its induction of cell autophagy. Based on accumulating evidence that inhibition of autophagy can enhance the efficiency of antitumor drugs ( 22 ), we combined NVP-BEZ235 with autophagy inhibitors for further verification.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, an increase of LC3II/I ratio was found in both LSCC cell lines treated with PI3K or mTOR inhibitors, among which the dual inhibitor NVP-BEZ235 is the most significant, supporting its induction of cell autophagy. Based on accumulating evidence that inhibition of autophagy can enhance the efficiency of antitumor drugs ( 22 ), we combined NVP-BEZ235 with autophagy inhibitors for further verification.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an increase of LC3II/I ratio was found in both LSCC cell lines treated with PI3K or mTOR inhibitors, among which the dual inhibitor NVP-BEZ235 is the most signi cant, supporting its induction of cell autophagy. Based on accumulating evidence that inhibition of autophagy can enhance the e ciency of antitumor drugs [33][34][35], we combined NVP-BEZ235 with autophagy inhibitors for further veri cation. Surprisingly, the combination of NVP-BEZ235 with two autophagy inhibitors (3-MA, CQ) showed a synergetic antitumor effect in both cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, microtubule-associated protein 1A/1B-light chain 3 (LC3) is transformed from the LC3-I (cytosolic form) to the LC3-II (autophagosome membranes-associated form) [ 79 , 80 ]. Increased LC3-II and decreased p62, a substrate of autophagy, indicate the normal autophagic flux that induces protein degradation and damaged organelle removal [ 81 ] ( Figure 3 ). In the SNL model, beclin-1, which is a key factor in the VPS34 complex, and LC3, in the ipsilateral spinal dorsal horn, are upregulated on day 7 and maintained for 14 days, suggesting that nerve injury triggers autophagy [ 82 , 83 ].…”
Section: Downstream Signals Of Ampk In Pain Regulationmentioning
confidence: 99%